2009
DOI: 10.4103/0255-0857.53203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bactec Mgit 960 Tb System for Recovery and Identification of Mycobacterium Tuberculosis Complex in a High Through Put Tertiary Care Centre

Abstract: MGIT 960 system with PNBA assay for identification of M. tuberculosis complex is a rapid and useful method in laboratories processing a large number of specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 14 publications
5
38
2
Order By: Relevance
“…Indeed, even though the LJ and the Coletsos medium were counted together as a single system, only 77 (78.5%) isolates of MTBC were recovered, in contrast to 92 (93.8%) isolates with the MGIT 960 system. These results are in accordance with those of other studies dealing mainly with pulmonary specimens [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, even though the LJ and the Coletsos medium were counted together as a single system, only 77 (78.5%) isolates of MTBC were recovered, in contrast to 92 (93.8%) isolates with the MGIT 960 system. These results are in accordance with those of other studies dealing mainly with pulmonary specimens [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…Almost 19% of the samples were positive by LJ after eight weeks highlighting the importance of solid media incubation for a longer time (at least 10-12 weeks). For LJ medium, similar TTD were observed by Rodrigues et al which time positivity of MGIT960 was 91% during the first 2 weeks and only 4% for the LJ medium [15].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While liquid culture techniques have been shown to have a higher yield and shorter time to detection of MTBC than solid media such as LJ, liquid culture methods are technically demanding and remain costprohibitive for routine use in many high-burden countries [35,36] . One challenge frequently encountered with routine use of liquid culture methods is the increase in overgrowth of bacterial contaminants compared to LJ [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Scores of studies including at national TB control program level across the globe have compared the added advantages of automated liquid culture over solid culture, to cite a few a department health study conducted at Bangkok, Thailand (n = 2566) showed 53% positive on liquid culture vs 39% in solid culture with time to detection shortened to 11 days vs 27 days, respectively, with significant value addition [8]; another Indian study showed 41% culture positive in MGIT culture vs 24% in solid culture with time to detection of 9 days vs 38 days, respectively (n = 14,957). In the Indian study, MGIT showed its significant value addition in case of sputum smear negative samples with 18% positivity by MGIT vs 1% over solid culture with time to detection of 16 days vs 48 days, respectively [9]. There are also reported evidences from comparative evaluation for Mtb complex and NTM in liquid culture (MGIT 960) vs solid culture (LJ/Ogawa) clearly indicating substantial added value of liquid culture in terms of sensitivity as well as reduced time to detection [10].…”
Section: Current Toolsmentioning
confidence: 94%